The Influence of Total Assets Turnover, Return on Assets and Debt To Equity Ratio on Stock Prices Moderated By Firm Size In Transportation And Logistics Companies Listed On The Indonesia Stock Exchange In 2019 – 2023 - Salza Adzri Arismutia (Journal of Accounting Inaba, 2024)
The study aims to determine the impact of TATO, ROA, and DER on Stock Prices, with Firm Size as a moderating. This research used secondary data acquired from the official website of the Indonesia Stock Exchange, www.idx.co.id. This research used quantitative methods, namely descriptive and verification methodologies. The study's population consisted of 32 Transportation Companies that were listed on the Indonesia Stock Exchange between 2019 and 2023. This research used a non-probability selection method called purposive sampling to choose 6 organizations as samples. The data were analyzed using the IBM SPSS 26 software. The study's findings demonstrated that the TATO, ROA, and DER variables had a favorable influence on stock prices. Firm Size as a moderating had a distinct impact on each variable. The size of the firm did not have a moderating effect on the effects of TATO on stock prices. The impact of ROA on stock prices is enhanced by the size of the firm. The impact of the DER on Stock Prices is weakened by the size of the firm. The impact of TATO, ROA, and DER on stock prices was enhanced by the size of the firm. This finding implies that the Firm Size cannot moderate the relationship between TATO and stock price. Future research can replace Firm Size with PER as a moderating variable, to determine its effect on Stock Price. So that comparative results can be obtained to be useful for the development of science and the economy in Indonesia